Isolation and Enzymatic Degradation of Hemicellulose from Corncobs Waste - Fithri, Lailatul; Damayanti, Mamik; Ayu, Anna Kartika (Journal of Bio-Molecule Research and Engineering, 2022)
Corncobs are rich in hemicellulose, which has very important applications in the food industry and biofuels. Hemicellulose is a heteropolysacharide which contains hexosan such as glucan, mannan, galactan and pentosan such as xylan and arabinan. The aims of this research are determining the optimum condition of hemicellulose isolation and identifying enzymatic degradation products of hemicellulose. Hemicellulose is extracted from corn cobs using various NaOH concentrations and extraction times. Acetic acid was added to the mixture after hemicellulose A reflux process, whereas hemicellulose B was precipitated with ethanol 96%. Enzymatic hydrolysis is carried out using xylanolytic enzyme from a recombinant of E. coli DH5α. The yield of hemicellulose is nearly 64.74% (w/w) using NaOH 4 M for 2 h of extraction time. Based on High Performance Liquid Chromatography data indicating that the enzymatic hydrolysis products of hemicellulose A are xylose and arabinose. While xylose, arabinose, and xylooligosaccharide are hemicellulose B and unextracted hemicellulose hydrolysis products.